G‐CSF induces CD15+ CD14+ cells from granulocytes early in the physiological environment of pregnancy and the cancer immunosuppressive microenvironment. Issue 5 (17th May 2022) - Maneta, Ebtehag; Fultang, Livingstone; Taylor, Jemma; Pugh, Matthew; Jenkinson, William; Anderson, Graham; Coomarasamy, Arri; Kilby, Mark D; Lissauer, David M; Mussai, Francis; De Santo, Carmela
Abstract: Objectives: Recombinant granulocyte colony‐stimulating factor (G‐CSF) is frequently administered to patients with cancer to enhance granulocyte recovery post‐chemotherapy. Clinical trials have also used G‐CSF to modulate myeloid cell function in pregnancy and inflammatory diseases. Although the contribution of G‐CSF to expanding normal granulocytes is well known, the effect of this cytokine on the phenotype and function of immunosuppressive granulocytic cells remains unclear. Here, we investigate the impact of physiological and iatrogenic G‐CSF on an as yet undescribed granulocyte phenotype and ensuing outcome on T cells in the settings of cancer and pregnancy. Methods: Granulocytes from patients treated with recombinant G‐CSF, patients with late‐stage cancer and women enrolled on a trial of recombinant G‐CSF were phenotyped by flow cytometry. The ability and mechanism of polarised granulocytes to suppress T‐cell proliferation were assessed by cell proliferation assays, flow cytometry and ELISA. Results: We observed that G‐CSF leads to a significant upregulation of CD14 expression on CD15 + granulocytes. These CD15 + CD14 + cells are identified in the blood of patients with patients undergoing neutrophil mobilisation with recombinant G‐CSF, and physiologically in women early in pregnancy or in those treated as a part of a clinical trial. Immunohistochemistry of tumor tissue or placental tissue identified the expression of G‐CSF. The G‐CSF upregulates the release of reactive oxygen species (ROS) in CD15 + CD14 + cells leading to the suppression of T‐cell proliferation. Conclusions: G‐CSF induces a population of ROS + immunosuppressive CD15 + CD14 + granulocytes. Strategies for how recombinant G‐CSF can be scheduled to reduce effects on T‐cell therapies should be developed in future clinical studies. Abstract : G‐CSF physiologically drives granulocyte expansion and is also administered in recombinant form alongside chemotherapy or immunotherapy. We show that G‐CSF upregulates the release of reactive oxygen species (ROS) in a unique population of CD15 + CD14 + cells leading to the suppression of T‐cell proliferation.